KAJIAN PEMANFAATAN TANAMAN PORANG (Amorphophallus muelleri ) DALAM BIDANG PANGAN DAN KESEHATAN: Study Of The Use Of Porang Plants (Amorphophallus Muelleri) In The Field Of Food And Health - Elis Yani Sumartini1; Ardi Rustamsyah; Farid Perdana; Anita Khairunnisa (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2023)
The porang plant (Amorphophallus Muelleri) is one of the forest plants in Indonesia with fairly high productivity. Porang tubers contain water-soluble polysaccharides in the form of glucomannan. Glucomannan is a dietary fibre that is soluble in water. The relatively high content of glucomannan makes the porang plant a useful plant, one of which is in the fields of food and health. This journal review aims to examine the use of porang-derived products in the food and health sectors. Journal writing is done by collecting data from various sources obtained from several research journals on the internet such as Google Scholar and DOAJ. Based on the results of the journal review, it can be concluded that porang plants can be used to influence texture in the manufacture slot maxwin of food products such as food bars, white bread, noodles, meatballs, sausages, nuggets, and gelling agents. In addition, the porang plant can be used in the health sector as an ingredient for making capsule shells and emulsion stabilizers, which are used as an alternative diet for people with obesity and type 2 diabetes mellitus.